ANALISIS KEPUTUSAN MEMBELI PADA TOKO BAZAR DAN TOKO MURAH MELALUI EFEKTIVITAS PERIKLANAN PT. RADIO KUMALA SAMARINDA - ., Herliana (EKONOMIA, 2012)
The purpose of research to determine the effectiveness of advertising on the PT. Radio Kumala Samarinda as a marketing strategy and usefulness of this study for consideration in understanding the effectiveness of the advertising on the radio, and what things are considered essential to create effective at advertising on the radio.The formulation of the research problem is this empathy, persuasion, communication impact and influence on the decision to buy the Shops Bazar & Murah Shop with advertising effectiveness PT. Radio Kumala Samarinda?.Marketing Management is one of the main activities undertaken by the company to maintain the continuity of the company, to grow, and to make a profit.